Pengaruh Disiplin Kerja Terhadap Kinerja Pegawai Di Korem 091/Aji Surya Natakesuma - Rela Arlita Damayanti; Anwar Alaydrus; Rita Kalalinggi (Jurnal Ilmu Pemerintahan, 2021)
The purpose of this study was to find out the effect of work discipline on employee performance at Korem 091/Aji Surya Natakesuma. The data collection technique was through distributing questionnaires to 39 respondents. The data processing technique used in this study to determine the effect of the work discipline variable (X) on the performance variable (Y) is by using simple linear regression and the coefficient of determination. The results of calculations from simple linear regression analysis are as follows constant (a) of 5.041 and regression coefficient (b) of 0.492 with a positive regression coefficient value. It turns out that the effect of work discipline on employee performance can be seen in the coefficient of determination test where the coefficient of determination test shows that the coefficient of determination (R2) is 0.789 or 78.9%. So it can be said that 78.9% of the influence of employee performance is caused by work discipline. The results showed that the work discipline variable had a significant positive effect on employee performance at Korem 091/Aji Surya Natakesuma, so the hypothesis proposed was acceptable.